Methodology for climate-agriculture-gender-inequity hotspot mapping - CGIAR GENDER Platform (2021)
A methodology has been developed and used to map hotspot countries and sub-national areas where climate hazards, large concentrations of women participating agriculture and high women's vulnerability due to gender inequalities converge, by using representative socio-economic datasets. (See evidence link for details)